Plant cell separation and adhesion - Roberts, Jeremy A (Blackwell, 2012)
This is the first volume to focus exclusively on plant cell separation processes and to link improvements in our scientific understanding with methods that may allow us to manipulate cell separation and adhesion to the benefit of the agricultural and horticultural industries.